The poor performance of foreign bank subsidiaries: Were the problems acquired or created? - Peek, Joe; Rosengren, Eric S.; Kasirye, Faith (Journal of Banking & Finance, 1999)
We examine foreign acquisitions of United States banks around the time of the ownership change to determine whether the observed poor performance of foreign subsidiaries is the result of changes in business strategy or the preexisting characteristics of the target bank. We find that many of the problems were already present at the time of acquisition. However, changes in business strategy by the foreign owners were generally not successful in raising the bank’s performance level to that of its domestic peers.